Elevated Hippocampal Cholinergic Neurostimulating Peptide precursor protein (HCNP-pp) mRNA in the amygdala in major depression - Bassi, Sabrina Cecilia (2015)
The amygdala is innervated by the cholinergic system and is involved in major depressive disorder (MDD). Evidence suggests a hyper-activate cholinergic system in MDD. Hippocampal Cholinergic Neurostimulating Peptide (HCNP) regulates acetylcholine synthesis. The aim of the present work was to investigate expression levels of HCNP-precursor protein (HCNP-pp) mRNA and other cholinergic-related genes in the postmortem amygdala of MDD patients and matched controls (females: N=16 pairs; males: N=12 pairs), and in the mouse unpredictable chronic mild stress (UCMS) model that induced elevated anxiety-/depressive-like behaviors (females: N=6 pairs; males: N=6 pairs). Results indicate an up-regulation of HCNP-pp mRNA in the amygdala of women with MDD (p<0.0001), but not males, and of UCMS-exposed mice (males and females; p=0.037). HCNP-pp protein levels were investigated in the human female cohort, but no difference was found. There were no differences in gene expression of acetylcholinesterase (AChE), muscarinic (mAChRs) or nicotinic receptors (nAChRs) between MDD subjects and controls or UCMS and control mice, except for an up-regulation of AChE in UCMS-exposed mice (males and females; p=0.044). Exploratory analyses revealed a baseline expression difference of cholinergic signaling-related genes between women and men (p<0.0001). In conclusion, elevated amygdala HCNP-pp expression may contribute to mechanisms of MDD in women, potentially independently from regulating the cholinergic system. The differential expression of genes between women and men could also contribute to the increased vulnerability of females to develop MDD.